A case report of mucinous adenocarcinoma derived from intra-ampullary papillary-tubular neoplasm with a malignant course - Hiroaki Fujita; Keinosuke Ishido; Norihisa Kimura; Taiichi Wakiya; Hayato Nagase; Tadashi Yoshizawa; Toshihiro Haga; Shintaro Goto; Hiroshi Kijima; Kenichi Hakamada (Surgical Case Reports)
Abstract Background Intra-ampullary papillary-tubular neoplasm (IAPN) has been classified as a Vater papillary tumor. The prognosis of IAPN is generally relatively good. Here, we describe a patient with a mucinous adenocarcinoma cluster in the Vater papilla of IAPN origin. Clinical presentation The patient was a 66-year-old man who was admitted to our hospital after a diagnosis of pancreatic head carcinoma based on a pancreatic duct dilatation found on abdominal ultrasound. CT showed a 40 mm lesion in the pancreatic head and expansion of the main pancreatic duct to a maximum diameter of 9 mm on the caudal side of the lesion. The extrahepatic bile duct had also expanded to a maximum diameter of 8 mm. PET/CT showed fluorodeoxyglucose (FDG) accumulation of SUVmax 6.02 that corresponded to the tumor in the pancreatic head, though it did not suggest distant metastasis. The patient was diagnosed with pancreatic head carcinoma T3 N0 M0 Stage IIA and underwent a pancreaticoduodenectomy. Pathology indicated that the tumor in the pancreatic head was a benign inflammatory lesion. On the other hand, the papillotubular tumor pervading the lumen in the duodenal papillary common channel met the criteria for IAPN, and a mucinous adenocarcinoma cluster found in the surrounding stroma suggested malignant transformation of IAPN. No metastasis to lymph nodes was demonstrated. With regard to the mucus phenotype of each lesion, the IAPN was MUC2 and MUC5AC positive, while the mucinous adenocarcinoma was MUC2-positive and MUC5AC-negative. In addition, CD10 was negative in both lesions, suggesting that mucus transformation from the gastric type to the intestinal type was a key element. A blood test 10 months after surgery showed increased CA19-9 (105 U/mL) and CEA (7.1 ng/mL). Abdominal CT showed multiple cystoid nodes in the liver, which were diagnosed as multiple liver metastases of mucinous adenocarcinoma transformed from the IAPN. Conclusions We reported a case with IAPN that developed in the Vater papilla, which took an extremely malignant course. IAPN generally has a good prognosis, but it is important to understand that a malignant course may occur.